Midlatitude mesosphere and lower thermosphere variations during the extreme gannon geomagnetic storm in May 2024 - Yuan, Tao; Pautet, P. D.; Taylor, M. J. (Frontiers in Astronomy and Space Sciences, 2025)
Recent studies based upon both observations and numerical simulations have indicated the impacts of the intense geomagnetic storms induced by Coronal Mass Ejections (CMEs) on the neutral dynamics in the mesosphere and lower thermosphere (MLT). Even in the midlatitude MLT, far equatorward of subauroral zone, significant variations were reported. Aurora is one of the major dynamic drivers in the MLT in high latitudes, but observations of the neutral dynamic variations under the aurora in the storm time MLT are sparse. The lack of such MLT observations during the presence of aurora leads to a critical gap in the understanding of upper atmospheric dynamics. In this paper, we present the unprecedented observations under the aurora during the Gannon Geomagnetic Storm in May 2024 by the Na Doppler lidar at Utah State University (42°N, 112°W) and the Advanced Mesospheric Temperature mapper (AMTM) at the nearby Bear Lake observatory (BLO). Significant warming (as much as ∼50 K) accompanied by fast equatorward flow in the lower thermosphere (up to ∼100 m/s changes in the meridional wind above 100 km altitude) were observed. The temperature enhancement (∼10 K) of the hydroxyl layer during the same period is also captured by the AMTM. Intriguingly, significant storm time depletion of sodium (Na) abundance on the topside of the mesospheric Na layer above 105 km, as much as more than 80%, was also observed. These observations provide insight for future investigations on the MLT responses to the intense geomagnetic storms, especially the role of aurora in these events.